Protein Residues and a Novel Motif Involved in the Cellular Localization of CheZ in Azorhizobium caulinodans ORS571 - Liu, Xiaolin; Liu, Yanan; Johnson, Kevin Scot; Dong, Xiaoyan; Xie, Zhihong (Frontiers in Microbiology, 2020)
Abstract Chemotaxis is essential for the competitiveness of motile bacteria in complex and harsh environments. The localization of chemotactic proteins in the cell is critical for coordinating a maximal response to chemotactic signals. One chemotaxis protein with a well-defined subcellular localization is the phosphatase CheZ. CheZ localizes to cell poles by binding with CheA in Escherichia coli and other enteric bacteria, or binding with a poorly understood protein called ChePep in epsilon-Proteobacteria. In alpha-Proteobacteria, CheZ lacks CheA-binding sites, and its cellular localization remains unknown. We therefore determined the localization of CheZ in the alpha-Proteobacteria Azorhizobium caulinodans ORS571. A. caulinodans CheZ, also termed as CheZAC, was found to be located to cell poles independently of CheA, and we suspect that either the N-terminal helix or the four-helix bundle of CheZAC is sufficient to locate to cell poles. We also found a novel motif, AXXFQ, which is adjacent to the phosphatase active motif DXXXQ, which effects the monopolar localization of CheZAC. This novel motif consisting of AXXFQ is conserved in CheZ and widely distributed among Proteobacteria. Finally, we found that the substitution of phosphatase active site affects the polar localization of CheZAC. In total, this work characterized the localization pattern of CheZ containing a novel motif, and we mapped the regions of CheZAC that are critical for its polar localization.